Further insights into the growth mechanism of the non-stoichiometric θ-Ni2Si phase. (May 2021) - Tellouche, G.; Mangelinck, D.; Hoummada, K.; Derafa, A.
Abstract: The solid state reaction of 50 nm Ni with Si(100) substrate was investigated using in situ X-ray diffraction (XRD). The sequence is simultaneous; it begins by δ-Ni2 Si phase then the metastable θ-Ni2 Si phase is formed. Both phases grow simultaneously. The growth mechanism of the non-stoichiometric θ-Ni2 Si phase is discussed on the basis of the evolution of its XRD peak during annealing. The results show that, during its growth, the non-stoichiometric θ-Ni2Si phase is split into two regions of different concentrations. This "original" behavior is justified by the discontinuous variation with composition of both the diffusion coefficient and the d-lattice spacing through the θ-Ni2 Si phase. Highlights: The growth mechanism of the non-stoichiometric θ-Ni2 Si phase is investigated. The θ-Ni2 Si XRD peak is split into two peaks. A discontinuous variation of θ-Ni2 Si(110) spacing versus Ni composition. The diffusion coefficient of θ-Ni2 Si goes through minimum for an intermediate Ni composition.